2017
DOI: 10.1159/000479091
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Antagonistic Interactions between Commensal Oral Streptococci and Streptococcus mutans

Abstract: Arginine metabolism via the arginine deiminase system (ADS) of oral bacteria generates ammonia, which can increase the pH of oral biofilms and decrease the risk for dental caries. Antagonistic interactions between ADS-positive and cariogenic bacteria in oral biofilms may be an important ecological determinant of caries. This study investigated the antagonistic potential and mechanisms of clinical isolates of arginolytic streptococci on and by Streptococcus mutans UA159, a well-characterized cariogenic human is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 54 publications
(82 reference statements)
0
70
0
Order By: Relevance
“…It is important to note that tobacco smoke promotes biofilm growth of oral pathogens, including P. gingivalis, and S. mutans [22,58,[61][62][63][64]. The three commensal species in this study have been shown to arrest the growth of common pathogens [16,17,65]. Furthermore, S. mitis can help promote the development of Th17 T cells that can cross-react with Streptococcus pneumoniae, enhancing the immune response against this pathogen and consequently leading to its clearance [66].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It is important to note that tobacco smoke promotes biofilm growth of oral pathogens, including P. gingivalis, and S. mutans [22,58,[61][62][63][64]. The three commensal species in this study have been shown to arrest the growth of common pathogens [16,17,65]. Furthermore, S. mitis can help promote the development of Th17 T cells that can cross-react with Streptococcus pneumoniae, enhancing the immune response against this pathogen and consequently leading to its clearance [66].…”
Section: Discussionmentioning
confidence: 92%
“…In addition, the individual components of flavorless E-liquid (i.e., nicotine, PG, and VG), when analyzed separately, also showed no significant effects on the growth of the three species tested. A potential implication of these results is that flavorless E-liquids and their generated aerosol induce less tooth decay and periodontal disease than traditional cigarette smoke, especially since oral commensals are known to arrest the growth of common pathogens [16][17][18] known to induce dental caries [23,24], promote periodontitis [25][26][27], and increase the risk for atherosclerosis-related events [28][29][30]. If this is true, a case for improving oral health (and overall health) could be made by federal health regulatory agencies for promoting the use of electronic nicotine delivery systems over the use of traditional cigarettes as a means of harm reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative and functional genomic analyses currently being performed on these and other recent isolates of S. sanguinis could shed more light on the cause of these distinct phenotypes. In a separate study that focused on the effects of arginine on the antagonistic interactions between oral commensals and S. mutans, it was shown that enormous diversity exists among commensal streptococci, both in their antagonistic capabilities and their susceptibility to S. mutans (48). Clearly, probing the basis for phenotypic variation among commensals and pathogens (49) remains an essential goal in efforts to improve caries risk assessment and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the proportions of cariogenic bacteria under acidic conditions promotes the lower diversity of organisms within the biofilms and demineralization of the tooth enamel (12). Exploring the interactions between these health-associated commensals and acidogenic bacteria is critical for our understanding of the pathogenic potential of S. mutans and for the development of novel therapeutic interventions, e.g., probiotic strains that antagonize the growth of S. mutans through multiple pathways (32,39). The construction and use of the various streptococcal fluorescent strains described here should allow for better insight into the behaviors of multispecies biofilms.…”
Section: Discussionmentioning
confidence: 99%